Implementing Total Quality Management Principles in The Apparel Manufacturing Sector: Ghana in Perspective (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study focused on understanding the implementation of TQM in the apparel manufacturing sector. Due to the lack of TQM studies in Ghana and especially in the apparel manufacturing business, there was a need to conduct a study to reposition the operational strategies in the apparel sector in Ghana.A mixed-method approach was employed to attain valid, reliable and reproducible conclusions. The population focused on apparel manufacturing firms in Ghana. Questionnaires and interviews were employed to gather data.The key findings indicate that the fundamental obstacle to implementing TQM was the lack of knowledge and misunderstanding of TQM principles and their benefits by both owners and workers alike, as well as outdated technology and poor infrastructure. Again, in the context of Ghana, financial constraints posed a significant challenge.